Examining the Social Involvement of Sports Civic Organizations - Madarász, Tamás; Szabados, György Norbert (International Journal of Engineering and Management Sciences, 2021)
Analyzing the information available in the Hungarian database of the CSO, we can see that a significant part of the income of classical non-governmental organizations, especially non-governmental organizations with a sports profile, comes mainly from state or private support. In addition, it can be said that these organizations are essentially non-profit-oriented and play a significant role in social integration and the performance of essential social tasks. Therefore, the relevant question is to what extent and in what way their social embeddedness is realized, in what way do NGOs influence people in the course of their operation? Within this, the study of the social usefulness of sports non-governmental organizations and the sphere of support conditions in the sphere emerges as a priority area. In our study, we undertake to examine the activity of the organizations included in the survey, their social impact and to compare the results with their role in local society. Nearly 50% of the NGOs surveyed in the study have a local scope, and more than 50% typically engage in grassroots and leisure-related activities.